Fine-mapping and cell-specific enrichment at corneal resistance factor loci prioritize candidate causal regulatory variants - Xinyi Jiang (Nature Portfolio, 2020)
Here, the authors report a genome-wide association analysis for corneal resistance factor (CRF), a measure of corneal biomechanical properties relevant to a number of corneal diseases. They identify 135 loci associated with CRF and use fine-mapping and ATAC-seq in human cornea cell lines to identify putative causal variants affecting gene expression.